How Pesaḥ and Maṣṣot Became Connected with the Exodus: The Development of the Festival Etiologies in Exod. 12:1–13:16 - Berner, Christoph (Religions, 2023)
The connection between the festival of Pesaḥ-Maṣṣot and the Israelites’ exodus from Egypt is a cornerstone of Jewish identity and religious practice which has its roots in the festival calendars of the Pentateuch (Exod. 12–13; Exod. 23; Lev. 23; Deut. 16). However, a closer investigation shows that the texts in question differ considerably both with respect to the characteristics of the festival and its etiological connection with the exodus. The present paper focuses particularly on the complex, and in parts contradictory, festival ordinances in Exod. 12:1–13:16 and argues that the present form of the passage results from a multi-step process of supplementation and revision. In this process, the once separate festivals of Pesaḥ and Maṣṣot were gradually merged to a single celebration which, in turn, led to various adjustments of their etiological connection to the events of the exodus.